Ask Question
2 April, 16:41

12 = - 4 (-6x - 3) + 24

+1
Answers (1)
  1. 2 April, 16:48
    0
    x = - 1

    Step-by-step explanation:

    Solve for x:

    12 = 24 - 4 (-6 x - 3)

    -4 (-6 x - 3) = 24 x + 12:

    12 = 24 x + 12 + 24

    Grouping like terms, 24 x + 12 + 24 = 24 x + (12 + 24):

    12 = 24 x + (12 + 24)

    12 + 24 = 36:

    12 = 24 x + 36

    12 = 24 x + 36 is equivalent to 24 x + 36 = 12:

    24 x + 36 = 12

    Subtract 36 from both sides:

    24 x + (36 - 36) = 12 - 36

    36 - 36 = 0:

    24 x = 12 - 36

    12 - 36 = - 24:

    24 x = - 24

    Divide both sides of 24 x = - 24 by 24:

    (24 x) / 24 = (-24) / 24

    24/24 = 1:

    x = (-24) / 24

    The gcd of - 24 and 24 is 24, so (-24) / 24 = (24 (-1)) / (24*1) = 24/24*-1 = - 1:

    Answer: x = - 1
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “12 = - 4 (-6x - 3) + 24 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers